Physics of Spin in Solids: Materials, Methods and Applications - Halilov, Samed; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
Most recent publications on spin-related phenomena focus on technological aspects of spin-dependent transport, with emphasis on the specific needs of spintronics. The present publication targets rather fundamental problems related to the physics of spin in solids, such as: (1) manifestation of spin and orbital polarization in spectroscopy, including valence and X-ray photoemission, magneto-optics, low-energy electron scattering on the surface; (2) application of new methods for interpretation and determination of magnetic low-lying excitations in the bulk and on the surface; (3) recent progress in evaluation of different type of magnetic forces including spin-orbit and exchange interaction, with subsequent determination of anisotropy and spin-ordering structure; (4) general problems of spin-dependent transport in semiconductors and metals, such as current-caused torque effect on spins at interfaces and spin injection in quantum dot systems; (5) problems in understanding the spin-dependent trends in unconventional superconductors; (6) many-body problems in solid state physics and recent progress in evaluation of self-energy effects; (7) fabrication of new magnetic materials with pre-programmed properties based on assembly from nano-particles, etc.
Fulde-Ferrell-Larkin-Ovchinnikov-Like State in Ferromagnet-Superconductor Proximity System -- Exchange Force Image of Magnetic Surfaces -- Spin-Dependent Tunnel Currents for Metals or Superconductors With Charge-Density Waves -- Electronic Structure of Strongly Correlated Materials: Towards a First Principles Scheme -- Spin-Density Wave and Short-Range Oscillations in Photoemission from Films of CR Metal -- The Role of Hydration and Magnetic Fluctuations in The Superconducting Cobaltate -- Holstein-Primakoff Representation for Strongly Correlated Electron Systems -- Tuning the Magnetism of Ordered and Disordered Strongly-Correlated Electron Nanoclusters -- Density Functional Calculations Near Ferromagnetic Quantum Critical Points -- Interplay Between Helicoidal Magnetic Ordering and Superconductivity on the Differential Conductance in HoNi2B2C/Ag Junctions -- Ab Initio Calculations of the Optical and Magneto-Optical Properties of Moderately Correlated Systems: Accounting for Correlation Effects -- Spin-Dependent Transport in Phase-Separated Manganites -- New Magnetic Semiconductors on the Base of TlBVI-MeBVI Systems (ME-FE, CO, NI, MN; B-S, SE, TE) -- Localized Magnetic Polaritons in the Magnetic Superlattice with Magnetic Impurity -- Spin Stability and Low-Lying Excitations in Sr2RuO4.
Keywords: PHYSICS; CONDENSED MATTER; MAGNETISM; SURFACES (PHYSICS).; PHYSICS; CONDENSED MATTER; MAGNETISM, MAGNETIC MATERIALS; SURFACES AND INTERFACES, THIN FILMS